Manajemen Mutu Pendidikan di MTs Negeri 8 Kebumen - Tursini Tursini; Eliyanto Eliyanto (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
The education quality management system is implemented at MTs Negeri 8 Kebumen. One part of a formal institution that is required to make continuous efforts to improve the quality of education. The implementation of the education quality management system is carried out in seven lines consisting of curriculum, student affairs, facilities and infrastructure, public relations, library, administration, and counseling. Efforts to improve the quality of education are carried out by implementing several policies, namely: (1) Policy to improve the quality of education in the field of learning which is carried out through learning by implementing the Moving Class system, increasing IT mastery, developing the Internet/HOT SPOT network; (2) Policy to improve the quality of student education by optimizing extracurricular activity programs and increasing the internalization of entrepreneurship; (3) Policy to improve the quality of education in the field of personnel by implementing periodic and routine upgrading programs, training, seminars, and MGMP for teachers and education staff, as well as providing facilities and financial assistance for teachers to carry out PTK.